On Subgroups of Prime Order in a Finite Group - Al-Sharo, K. A.; Shemetkov, L. A.; Аль-Шаро, X. А..; Шеметков, Л. А.; Аль-Шаро, X. А..; Шеметков, Л. А. (Institute of Mathematics, NAS of Ukraine, 2002)
We study finite groups with generalized normality condition for subgroups of prime order.